Willow sculpture at the Rovaniemi University of Applied Sciences - photograph ... - Campbell, Sandy (University of Alberta Library, 2011)
This willow over wire globe sculpture was located outside the entrance to the Rovaniemi University of Applied Sciences, Rantavitikka Campus. The six protrusions at the top of the sculpture echo the symbol of the University, which can be partially seen on the glass of the entry behind the sculpture. The sculpture is a student project, part of a course of studies in natural product industry. ...